Rancangan Penerapan Sistem Keamanan Pangan ISO 22000 PT.X - Robert Sutjiono; Jani Rahardjo; Iwan Halim Sahputra (Jurnal Titra, 2022)
PT. X is a food packaging company. From interviews with the company reveals that it has not implemented the ISO 22000 because there is no commitment. The project aims to identify and complete the documents and deficiencies required for the ISO 22000:2018 certification. The documents and data needed for the design are obtained by interviewing workers at the company and observation. The first step is conformity analysis to the ISO to find out what percentage of the company's readiness. The second step is designing the required clauses. The initial gap is found 10.16%. Then the appropriate clauses will be directly included in the new design and those that have not been fulfilled will be redesign. The design is carried out for clause 4 to clause 10. After designing, the company’s readiness to conform the ISO 22000:2018 IS 84.4%. The results of the design show improvement so that the company can be considered ready to carry out certification.